lim ((x+h)^-2 - x^-2)/h as h->0 - Wolfram|Alpha
I don't know where the answer is coming from. What are the missing steps?
lim ((x+h)^-2 - x^-2)/h as h->0 - Wolfram|Alpha
I don't know where the answer is coming from. What are the missing steps?
$\displaystyle \lim_{h \to 0} \frac{\frac{1}{(x+h)^2} - \frac{1}{x^2}}{h}$
$\displaystyle \lim_{h \to 0} \frac{\frac{1}{(x+h)^2} - \frac{1}{x^2}}{h} \cdot \frac{x^2(x+h)^2}{x^2(x+h)^2}$
$\displaystyle \lim_{h \to 0} \frac{x^2 - (x+h)^2}{h \cdot x^2(x+h)^2}$
finish it ...